Association between Heat Stress, Work Fatigue, and Elevated Blood Pressure among Construction Workers in Yogyakarta - Kusuma, Nisa Nur; Sumardiyono, Sumardiyono; Murti, Bhisma (Journal of Health Policy and Management, 2022)
Background: Excessive heat stress will cause fatigue and drowsiness, reduce stability and increase the number of work errors. The purpose of this study was to analyze the relationship between heat stress and work fatigue and increased blood pressure in construction workers at PT PP Urban Development Project at the University of Nahdlatul Ulama Yogyakarta. Subjects and Method: Research with a cross sectional design was conducted at PT PP Urban Development Project, Nahdlatul Ulama University, Yogyakarta, from March to April 2022. A sample of 107 workers was selected by purposive sampling. The dependent variable is work fatigue and an in-crease in blood pressure. The independent variable is heat stress. Heat stress was measured by Heat Stress Monitor, work fatigue by reaction timer and increase in blood pressure was measured by digit-al sphygmomanometer. Test analysis using chi-square and the value of Odds Ratio (OR). Results: Construction workers who experience high heat stress have a risk for an increase in blood pressure of 3.10 times compared to normal heat stress and are statistically significant (OR= 3.10; 95% CI= 1.01 to 9.24; p= 0.020), and have a risk of work fatigue 2.73 times compared to normal heat stress and statistically significant (OR= 2.73; 95% CI= 0.97 to 7.52; p= 0.020). Conclusion: There is a relationship between high heat stress and work fatigue and an increase in blood pressure.Keywords: heat stress, fatigue, blood pressure Correspondence:Nisa Nur Kusuma. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A,Surakarta 57126, Central Java, Indonesia. Email: nisankusuma22@gmail.com. Mobile: +6282225229919 J Health Policy Manage. 07(01): 72-80. https://doi.org/10.26911/thejhpm.2022.07.01.07